New records of the family Thripidae (Thysanoptera, Terebrantia) from India - Abhishek Patidar; Shash Pal; Madhurima Sarma; Vikas Kumar; Kaomud Tyagi (Journal of Insect Biodiversity and Systematics, 2023)
Two species of family Thripidae, Hydatothrips onari Kudô, 1997 from subfamily Sericothripinae and Thrips alius Palmer, 1992 from subfamily Thripinae are collected on Guizotia abssinica and general vegetation respectively for the first time from India after their original description. Due to the addition of these two species in the Indian fauna, the number of species increased under the genus Hydatothrips from 10 to 11 and under the genus Thrips from 44 to 45. Species diagnosis with illustrations and distribution of the newly recorded taxa is also provided.